Development Strategy of the Bird Nest Adoption Program in the Community Forest of Jatimulyo Village, Kulon Progo Regency, Special Region of Yogyakarta - Rimba Bintoro; Leti Sundawati; Yeni Aryati Mulyani (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
The bird nest adoption program in Jatimulyo is one of the activities to protect birds from extinction. This activity is carried out by keeping birds that are breeding in nests in community forest habitats. The development of this concept was expected to protect the birds and increase the economic value of the community-owned forest from the non-timber sector that supported environmental sustainability. However, the program is not yet implemented in the whole area of Jatimulyo Village. This study aimed to determine the strategy for developing the bird nest adoption program in Jatimulyo Village. Data was collected through in-depth interviews with expert respondents with extensive experience and knowledge of the studied problems. The data that has been collected was analyzed using SWOT analysis. The SWOT analysis results showed that an offensive strategy is needed to develop the bird nest adoption program, which can be carried out by utilizing strengths to seize opportunities. There are five alternative strategies, i.e. (1) increase the number of nest findings to be adopted to increase people's incomes; (2) take advantage of the attention of the government and other institutions to strengthen farmer groups and support the management of adoption programs; (3) opening access to birdwatching special interest tours by involving the community as local guides; (4) encourage bird protection in the Jatimulyo area and jointly promote bird nest adoption program; and (5) expanding the adoption area in Jatimulyo Village. Keywords: bird nest adoption, community forest, development strategy, SWOT analysis